2021
DOI: 10.1093/g3journal/jkab291
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships and codon usage bias amongst cluster K mycobacteriophages

Abstract: Bacteriophages infecting pathogenic hosts play an important role in medical research, not only as potential treatments for antibiotic-resistant infections, but also offering novel insights into pathogen genetics and evolution. A prominent example are cluster K mycobacteriophages infecting Mycobacterium tuberculosis, a causative agent of tuberculosis in humans. However, as handling M. tuberculosis as well as other pathogens in a laboratory remains challenging, alternative non-pathogenic relatives, such as M. sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…In addition, based on the RSCU values of different species, we constructed the relationship between different Amanita and found that the relationship between different species based on RSCU was different from the sequence-based relationships. However, the genetic relationship between some species was correctly interpreted according to the RSCU value, which was consistent with other studies ( Crane et al, 2021 ; Gupta et al, 2021 ). The results show that the phylogenetic results based on RSCU can be an important supplement to the phylogenetic results based on sequence.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, based on the RSCU values of different species, we constructed the relationship between different Amanita and found that the relationship between different species based on RSCU was different from the sequence-based relationships. However, the genetic relationship between some species was correctly interpreted according to the RSCU value, which was consistent with other studies ( Crane et al, 2021 ; Gupta et al, 2021 ). The results show that the phylogenetic results based on RSCU can be an important supplement to the phylogenetic results based on sequence.…”
Section: Discussionsupporting
confidence: 90%
“…The relative synonymous codon usage (RSCU) of a range of Ganoderma species and strains was evaluated to identify relationships between them, which diverged from those established from sequence-based data. The RSCU value also accurately reflected the genetic connections between or within some Ganoderma strains or species, which was consistent with the findings of previous studies (Crane et al, 2021;Gupta et al, 2021;Li et al, 2022d). In general, this research has improved our understanding of codon usage characteristics and genetic evolution of this higher fungal group and other related fungal species.…”
Section: Optimal Codon Analysissupporting
confidence: 90%
“…For example, viruses frequently corrupt the translational machinery of their hosts to synthesize their own viral proteins [28], and this synthesis is generally more efficient if the codon usage patterns of the virus matches that of its host [29,30]. Taking advantage of this relationship, Crane, Versoza and colleagues [31] determined the codon usage bias of 129 mycobacteriophages across 14 putative mycobacterial hosts using COUSIN [32] to obtain important insights into putative mycobacterial host ranges in nature. Bacteriophage genomes can also acquire molecular characteristics of their hosts due to exposure to similar genome-wide mutational pressures, a process referred to as 'genome amelioration' [33][34][35].…”
Section: Alignment-free Methodsmentioning
confidence: 99%